The Effectiveness of Classical Music Therapy in Reducing Anxiety Among Senior-Level Students when Facing Their Final Assignments Among Public Health Students at Universitas Indonesia Maju in 2023 - Intan Puspita Asri; sari, Agustina (Universitas Nahdlatul Ulama Surabaya, 2024)
In 2019, approximately 301 million people worldwide lived with anxiety disorders, and 280 million people lived with depression. According to research conducted by the Center for Reproductive Health et al. (2022), anxiety disorders (26.7%) are the most prevalent mental health disorders experienced by adolescents, affecting both boys (25.4%) and girls (28.2%) in Indonesia. This study aimed to determine the effectiveness of classical music therapy in reducing anxiety among final-year public health students in 2023. The sample size for this research was 32 respondents. The research method used was a quasi-experimental design employing a non-equivalent control group design, with accidental sampling as the sampling technique. The pre-test and post-test results for the control group showed a p-value of 0.232, which means it is more significant than 0.05, indicating no effect. In contrast, the pre-test and post-test results for the experimental group displayed a p-value of 0.027, which is less than 0.05, indicating a significant impact. Thus, there was a difference in anxiety levels after applying classical music therapy among final-year public health students facing their final projects at Indonesia Maju University in 2023. In conclusion, classical music therapy is effective in reducing anxiety. Therefore, classical music therapy is expected to be one of the alternative methods for reducing stress, not only when completing final projects but also in other situations.